INTRODUCTION TO THE SPECIAL EDITION OF PINS - CONTEMPORARY RACISM: A CRITICAL REVIEW OF SOCIAL PSYCHOLOGICAL APPROACHES. - Durrheim, Kevin (PINS-Psychology in Society, 2026)
During the past 25 years a number of new approaches to studying the psychology of racism have been developed. Prior to this, the main focus was on the prejudiced personality. The early literature took bearings from Allport's (1954) classic, The nature of prejudice, accepting that prejudice was a cognitive distortion - "a faulty generalization" - that was based on negative affect or hatred of outgroups. Following the theory of authoritarianism (Adorno et al, 1950), prejudice was understood to be a stable and general trait, grounded in the personality of the prejudiced individual.